ISLAMIC ECO-THEOLOGY: Recycling Used Cooking Oil into Soap for Maṣlaḥah Oriented Families - Rosyadi, Salim; Raya, Fitri; Fitriyani, Nina; Syed Hassan, Syed Najihuddin (TAJDID: Jurnal Ilmu Ushuluddin, 2025)
This study explores the concept of ecological theology through the utilization of used cooking oil as a primary material in bar soap production and examines its implications for the development of maṣlaḥah-oriented families. Typically regarded as household waste, used cooking oil poses significant environmental risks if not properly managed. Therefore, this research seeks to investigate the theological values embedded in environmentally sustainable household waste management practices and to assess their social and ecological impacts on family well-being. Employing a descriptive qualitative approach grounded in Participatory Action Research (PAR), the study focuses on the Fatayat community in Serang Regency. The findings indicate that processing used cooking oil into soap can reduce household expenditures on cleaning products by approximately 3%. From an economic standpoint, this activity serves as an educational initiative for family members, fostering awareness in transforming waste into economic value, thereby providing additional income for families in Serang Regency. Environmentally, it contributes to reducing liquid waste pollution by converting it into environmentally friendly and utilitarian products. These outcomes are in line with the principles of maṣlaḥah (benefit), iʿtidāl (ecological justice), tahdhīb al-nafs (spiritual refinement), and tawāzun (balance between nature and humanity).